Pengembangan Video Animasi Interaktif Materi Menganalisis Informasi untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Fase C SD Muhammadiyah Kabupaten Luwu - Anugrah, Ega; Sukirman, Sukirman; Mirnawati, Mirnawati (Indo-MathEdu Intellectuals Journal, 2026)
Indonesian language learning in analysing information at primary school requires students to have critical thinking skills in understanding, interpreting, and drawing conclusions from texts. However, learning that is still dominated by conventional methods causes students to be less active and have difficulty identifying important information and providing logical reasons. One of the contributing factors is the limited use of interactive learning media. This study aims to develop interactive animated videos on the subject of analysing information to improve the critical thinking skills of Phase C students at SD Muhammadiyah Wiwitan, Luwu Regency. This study uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 25 fifth-grade students. Data collection techniques included observation, interviews, questionnaires, expert validation, and pre- and post-tests. The results showed that the interactive animated video developed was highly valid based on the assessment of subject matter and media experts. The practicality test showed that the responses of teachers and students were highly practical. In addition, the effectiveness test showed an increase in students' critical thinking skills based on a comparison of pretest and posttest results.